2007
DOI: 10.1007/s10554-007-9275-z
|View full text |Cite
|
Sign up to set email alerts
|

CFD analysis in an anatomically realistic coronary artery model based on non-invasive 3D imaging: comparison of magnetic resonance imaging with computed tomography

Abstract: Computational fluid dynamics (CFD) methods based on in vivo three-dimensional vessel reconstructions have recently been shown to provide prognostically relevant hemodynamic data. However, the geometry reconstruction and the assessment of clinically relevant hemodynamic parameters may depend on the used imaging modality. This study compares geometric reconstruction and calculated wall shear stress (WSS) values based on magnetic resonance imaging (MRI) and computed tomography (CT). Both imaging methods were appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 34 publications
4
22
0
Order By: Relevance
“…However, a quantitative comparison is difficult to be made, as they have used a considerably different input flux, more broadly distributed over time. A similar range of wall shear rates is also reported by Goubergrits et al [64]. Regarding qualitative changes in the WSS values observed over the LAD and LCX arteries in the above studies, suffice it to mention that similar trends to those observed in this work have been reported, with the maximum shear stress obtained at the peak of the pulse at the end of the LCX (compare our Figure 6(b) for t = 0.075 with the middle row, last column in Figure 4 of [42] and Figure 7 of [64]).…”
Section: Physiological Left Coronary Artery Bifurcationsupporting
confidence: 88%
“…However, a quantitative comparison is difficult to be made, as they have used a considerably different input flux, more broadly distributed over time. A similar range of wall shear rates is also reported by Goubergrits et al [64]. Regarding qualitative changes in the WSS values observed over the LAD and LCX arteries in the above studies, suffice it to mention that similar trends to those observed in this work have been reported, with the maximum shear stress obtained at the peak of the pulse at the end of the LCX (compare our Figure 6(b) for t = 0.075 with the middle row, last column in Figure 4 of [42] and Figure 7 of [64]).…”
Section: Physiological Left Coronary Artery Bifurcationsupporting
confidence: 88%
“…Note that similar model (silicon model based on the same original geometry, but with other up scaling) was also acquired by CT and MRI in our earlier study. 16 All techniques are able to reproduce LCA geometry well with an error that is about the resolution of the respective technique (voxel size). For biplane angiography, the voxel size definition is of cause not possible.…”
Section: Geometrymentioning
confidence: 99%
“…Though wall thickness is an important parameter in assessing atherosclerosis it has no direct impact on the calculation of WSS. Recently, we evaluated a simplified approach to 3D-modelling of the geometry of coronary arteries based on biplane angiograms only 16 that allows retrospective studies in angiographic databases. Improvements in imaging modalities (multi-slice CT and MRI) provide alternative noninvasive data sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These errors are in the range of the resolution of the CT scan. When translated to in vivo size, the mean surface distance error amounts to approximately 90 lm, which is smaller than that reported by Goubergrits et al (2009) from biplane angiography (232 lm) or Doorly et al (2008) (290 lm), and similar to that reported in (Goubergrits et al 2008) from MRI (100 lm).…”
Section: Fidelity Of the Phantom To The Digital Modelmentioning
confidence: 46%